Surgical treatment of synkinesis between smiling and eyelid closure. Issue 12 (December 2017) - Biglioli, Federico; Kutanovaite, Otilija; Rabbiosi, Dimitri; Colletti, Giacomo; Mohammed, M.A.S.; Saibene, Alberto M.; Cupello, Silvia; Privitera, Antonino; Battista, Valeria M.A.; Lozza, Alessandro; Allevi, Fabiana
Abstract: Synkinetic movements are common among patients with incomplete recovery from facial palsy, with reported rates ranging from 9.1% to almost 100%. The authors propose the separation of the neural stimulus of the orbicularis oculi from that of the zygomatic muscular complex to treat eyelid closure/smiling synkinesis. This technique, associated with an anastomosis between the masseteric nerve and a central branch of the facial nerve, as well as with the use of a cross-facial nerve graft, resolves most of the spasms of the midface musculature, leading to a more relaxed tone when the mimic muscle is at rest and enhancing muscle excursion during voluntary and spontaneous smiling. Between 2011 and 2016, 18 patients affected by segmental paresis of the middle of the face underwent surgical treatment at the Maxillofacial Surgery Department of the San Paolo Hospital (Milan, Italy). Of these patients, 72.22% of cases with hypertone obtained partial to complete relaxation. Synkinesis was completely resolved in 83.33% of cases, and a significant improvement in facial movement was achieved in all patients. Neurorrhaphy of the masseteric nerve and the central branch of the facial nerve appears to produce favorable results. These initial data should be confirmed by further studies.